Studi Kelayakan Rencana Pengembangan Pembangunan Gedung F Universitas Dr. Soetomo Surabaya - Hastono, Klotok Budi; Apriliani, Rizki Astri; Bustamin, Maulidya Octaviani; Kuncaravita, Sekar Ayu (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2024)
Building F Dr. University Soetomo Surabaya has several main functions consisting of a Library Room, Lecturer Room, Classroom and Auditorium which has been established since 1981, so it is necessary to assess the condition of the building as material for further evaluation. The research was carried out with a building survey to review such as carrying out investigations on the building, measuring or checking. The results of the research obtained are, firstly, technical architecture including aspects of comfort, health, safety, Building F, Dr. University. Soetomo has fulfilled all assessment points well. Second, the structural technical test results obtained using the Hammer Test show that the average compressive strength value of concrete in the building structure of building F gives a value below 250 kg/cm2 which is the minimum concrete quality value used in building structures, so this shows that the strength of the concrete is not meets the requirements when used for multi-storey building structures. Third, the technical utility shows that the strong current electrical system functions well and can be operated safely. The main electrical equipment, labels on panels, good and neat electrical installation lines are not well organized, maintenance is needed to tidy up the electrical cable lines.